Senyawa Fucodiphlorethol Dan Phloroglucinol Alga Coklat Sebagai Inhibitor Lipase Secara In Silico - Yohanes Bare; Dewi Ratih Tirto Sari; Marsiana Coo Mogi; Maria Marcelina Dua Nurak (UNIVERSITAS PGRI MADIUN, 2022)
Brown algae is a marine functional food that high fibers, vitamins, and bioactive compounds. Brown algae improved blood glucose and lipid profile. This study investigated the potential activity of two bioactive compounds from brown algae, as anti-obesity through pancreatic lipase inhibition. Molecular docking was conducted for investigating the lipase inhibition of bioactive compounds. Lipase structure (PDB ID 1ETH) was obtained from protein data bank and docked with fucodiphlorethol and phloroglucinol in specific position. Then, the complex was analyzed by PyMol following by Discovery Studio version 21.1.1. Phloroglucinol - pancreatic lipase showed five amino acid residues by hydrogen bonds, hydrophobic and electrostatic. Â Fucodiphlorethol - pancreatic lipase generated binding energy -392 kJ/mol and consisted of eight hydrogen bonds, three electrostatic, and 4 hydrophobic interactions. The active sites of fucodiphlorethol and phloroglucinol with lipase were not considered as active sites or catalytic sites. Therefore, we predicted that both of fucodiphlorethol and phloroglucinol inhibit lipase allosterically by altering the protein structure conformations. molecular docking analysis suggested that fucodiphlorethol and phloroglucinol have potential antiobesity effect by inhibiting lipase. Molecular dynamic are needed for further investigation.